Developing a comprehensive assessment framework for experiential quality at internet celebrity check-in places: incorporating embodied theory in a quantitative approach - Danhe, Wang; Ab Aziz, Yuhanis bt; Shin Yiing, Lee (SAGE Publications, 2025)
The increasing popularity of Internet Celebrity Check-in Places has stimulated research interest in these emerging tourist destinations. However, previous studies have predominantly focused on psychological satisfaction, neglecting the significance of embodied factors, such as physical conditions. To bridge this research gap, the present study adopts an embodied framework to comprehensively evaluate the quality of tourism experiences at these destinations. Drawing on the theoretical foundations of embodiment, an original evaluation index system is developed, encompassing dimensions of physicality, perception, and situational factors. Objective online reviews and subjective interviews are collected from the Yundong Library case study in Haikou City and transformed into numerical scores. The findings reveal that tourists’ physical experiences are hindered by constraints, such as restrictive age policies. Additionally, sensory engagement and active participation receive relatively low scores, indicating areas for improvement. While the perception of distinctive scenic attributes is positive, reception conditions, including dining and transportation, receive below-average ratings. By incorporating physical aspects into the evaluation, a more holistic assessment is achieved compared to conventional approaches. The standardized evaluation system provides destination managers with practical insights and a data-driven approach to benchmark strategies and enhance the quality of experiences over time. This study extends existing frameworks and underscores the importance of incorporating the embodied perspective in understanding and perpetuating experiences that hold essential value for the tourism industry.